2022
DOI: 10.1021/acs.jpcb.2c00996
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Carotenoid Dynamics via the Vibronic Energy Relaxation Approach

Abstract: Carotenoids are an integral part of natural photosynthetic complexes, with tasks ranging from light harvesting to photoprotection. Their underlying energy deactivation network of optically dark and bright excited states is extremely efficient: after excitation of light with up to 2.5 eV of photon energy, the system relaxes back to ground state on a time scale of a few picoseconds. In this article, we summarize how a model based on the vibrational energy relaxation approach (VERA) explains the main characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Could the excited state of the quencher be the S* state of Fxs as proposed for CP29/LHC-Astaxanthin? , S* was initially reported in the spirilloxanthin molecule, and later it was frequently observed in spheroidene, rhodopin glucoside, lycopene, zeaxanthin, and β-carotene . It has a characteristic excited state absorption that occurs generally as a shoulder between the carotenoid ground state bleaching and the major ESA peak due to the S 1 –S n transition. So far, the origin of the S* signal is still largely controversial. A previous work summarized that the S* state is essentially determined by the conjugation length of carotenoids; for longer molecules ( N > 11), the S* signal is the hot ground state, while for the shorter ones, the S* state corresponds to the S 1 state. , In the case of Fx, the effective conjugation length is only 8.1, so the S* state could thus be ruled out in our quenching scheme.…”
mentioning
confidence: 99%
“…Could the excited state of the quencher be the S* state of Fxs as proposed for CP29/LHC-Astaxanthin? , S* was initially reported in the spirilloxanthin molecule, and later it was frequently observed in spheroidene, rhodopin glucoside, lycopene, zeaxanthin, and β-carotene . It has a characteristic excited state absorption that occurs generally as a shoulder between the carotenoid ground state bleaching and the major ESA peak due to the S 1 –S n transition. So far, the origin of the S* signal is still largely controversial. A previous work summarized that the S* state is essentially determined by the conjugation length of carotenoids; for longer molecules ( N > 11), the S* signal is the hot ground state, while for the shorter ones, the S* state corresponds to the S 1 state. , In the case of Fx, the effective conjugation length is only 8.1, so the S* state could thus be ruled out in our quenching scheme.…”
mentioning
confidence: 99%
“…13,14 Recent analyses have shown that both explanations are likely valid with the hot ground state contribution dominating for long (N 4 12, N -number of conjugated CQC bonds) carotenoids, while the contribution from an excited state is important for shorter carotenoids. [15][16][17] Most of the spectroscopic studies targeting the properties of carotenoid excited states have been performed by following the dynamics after excitation of the S 2 state. Yet, when the absorption spectrum of a carotenoid is extended to the UV region, another absorption band appears in the 250-350 nm spectral region, and the exact peak position depends on the conjugation length.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Recent analyses have shown that both explanations are likely valid with the hot ground state contribution dominating for long ( N > 12, N – number of conjugated CC bonds) carotenoids, while the contribution from an excited state is important for shorter carotenoids. 15–17…”
Section: Introductionmentioning
confidence: 99%
“…The existence of a Car S* state with distinct photophysical properties is doubtless, but there are a few interpretations in the literature about its origin. 23,26,28,29,[44][45][46][47][48] The Car S* state has been associated with both a hot ground state signal, stemming from non-equilibrium vibronic populations, 49 , with the S 1 state in a specific conformation, 27,47 or with a twisting of the Car while in the excited state. 46 Finally, a combination of these different origins has been proposed to give rise to the S* features.…”
Section: Introductionmentioning
confidence: 99%